The Influence Of Servant Leadership On The Performance Among Kindergarten Teachers - Dini, Yuli Indah Fajar; Shirlyn, Shirlyn; Mon, Muhammad Donal (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This article aim to examine the influence of servant leadership on work engagement and affective commiment. which affect task performance among Kindergarten (TK) teachers in Batam City. The method used in this research is quantitative research with purposive sampling method. The sample in this study was taken from teachers working in kindergartens in Batam City. The researchers chose this sample because kindergarten teachers play a crucial role in providing foundational education to children before they move on to the next level of education. Data for this study were obtained from 337 respondents who filled out an online questionnaire, answering a total of 36 questions. Out of the seven hypotheses proposed in this study, all of them showed significant results. The findings of this study are consistent with previous research indicating that servant leadership significantly impacts the job engagement and affective commitment of kindergarten teachers in Batam City. This, in turn, significantly affects the performance of teachers in their duties. This type of leadership enables kindergarten teachers to fully carry out their tasks and responsibilities effectively. Additionally, teachers can utilize their abilities in school settings to make positive contributions to themselves and their organizations.